Variation under a psycholinguistic perspective: number agreement in Brazilian Portuguese and its impact for the schooling - Ana Paula da Silva Passos Jakubów; Letícia M. Sicuro Corrêa (Ilha do Desterro)
This paper discusses the impact of schooling in the production of number agreement in Brazilian Portuguese (BP) by 6th graders in Rio de Janeiro. Number agreement in BP can vary between: (a) redundant, the standard variety or (b) non-redundant, non-standard forms. Such variation is influenced by speakers’ socioeconomic status (SES) and educational level (Naro, 1981; Scherre & Naro, 1998 among many others). Results of an elicited production experiment carried out with 6th graders suggest influence of SES/ type of school and academic performance in language production; the effects of schooling and metalinguistic awareness are discussed. An account of language production is presented by conciliating L1 and L2 models of speech production, considering the possibility of the coexistence of varieties in a single speaker to be akin to bilingualism.